Toward Digital Population Administration: A Qualitative Analysis of the Implementation of Digital Identity Policies in the Transformation of Population Services - Fika Fibriyanita; Deli Anhar; Normajatun Normajatun; Riska Aulia Noor (Publikasi Indonesia, 2026)
The digital transformation of civil registration administration has become a key part of public service reform, particularly through the implementation of Digital Population Identity (IKD) to enhance service effectiveness, transparency, and accessibility. However, the implementation of IKD presents challenges related to organizational capacity, citizens' digital literacy, data security, and service acceptance at the user level. This study aims to analyze the implementation of IKD policy in civil registration services, identify its enabling and constraining factors, and examine its contribution to the dynamics of digital governance in civil administration. A qualitative approach with a case study strategy was used, focusing on civil registration services in a local Dukcapil office. Data were collected through semi-structured interviews, non-participant observation, and document analysis, and analyzed using reflexive thematic analysis to identify emerging patterns from the experiences of service officials and users. The findings reveal that IKD is seen as both a symbol of service modernization and a tool to accelerate administrative processes. However, its implementation heavily relies on the capacity of frontline officials to mediate technology, explain procedures, and solve operational issues. The practical benefits of IKD are mostly experienced by users with sufficient digital competence, while other groups face barriers such as access, device limitations, and hesitation to use digital services. Trust in IKD remains fragile due to concerns about data security, making service acceptance dependent on user interactions with officials and trust in public institutions.